Quality of primary care physicians’ communication of diabetes self-management during medical encounters with persons with diabetes mellitus in a resource-poor country - O. S. Ojo; S. O. Malomo; A. O. Egunjobi; A. O.A. Jimoh; M. O. Olowere (South African Family Practice)
Background: Most of the Nigerian studies on the determinants of diabetes self-management have focused on patient-related factors. There is no previous local study that examined the quality of diabetes self-management education provided by primary care physicians to people with diabetes mellitus. Methods: A descriptive cross-sectional study was conducted among 105 primary care physicians during a workshop. The quality of diabetes self-management education provided by the physicians was assessed using a self-designed scale of 39 Likert questions derived from American Association of Diabetes Educators seven domains of diabetes self-management. Cronbach’s reliability coefficient of each domain/subscale was ≥ 0.7. The data was analysed using the independent sample t-test and one-way ANOVA. Results: Over half of the physicians provided ‘inadequate quality’ diabetes self-management education in all the domains. Physicians had the highest mean score in the ‘taking medication’ domain (4.35 ± 0.59). The mean scores in the ‘problemsolving domain’ (3.63 ± 0.74) and the ‘being active domain’ (3.57 ± 0.71) were low. The quality of diabetes self-management education provided by the physicians was not associated with any of the physician characteristics. Conclusion: The quality of physicians’ communication of diabetes self-management was suboptimal in this study. The majority of the adequately communicated diabetes self-management behaviours were risk factors reduction related and disease-centred. Thus, training of primary care physicians on diabetes self-management education is recommended because of the key role these physicians play in diabetes management in resource-poor countries.